2021
DOI: 10.1039/d1ra01530c
|View full text |Cite
|
Sign up to set email alerts
|

Improved liquid–liquid extraction by modified magnetic nanoparticles for the detection of eight drugs in human blood by HPLC-MS

Abstract: High-performance magnetic Fe3O4@TiO2, nanospheres with mesoporous structures was synthesized for cleanup phosphatidic acid and fatty acids in blood sample for 8 drugs test with HPLC-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Functionalized MNPs could be used for drug detection in various biological fluids. Yang et al developed a TiO 2 -modified mesoporous magnetite nanoparticle for the detection of commonly used drugs in human blood [ 104 ] using a liquid–liquid extraction procedure. The authors concluded that the proposed procedure using modified magnetic nanoparticles has some advantages, among them being the minimization of blood matrix effects during analysis.…”
Section: Diagnostic Application Of Mnpsmentioning
confidence: 99%
“…Functionalized MNPs could be used for drug detection in various biological fluids. Yang et al developed a TiO 2 -modified mesoporous magnetite nanoparticle for the detection of commonly used drugs in human blood [ 104 ] using a liquid–liquid extraction procedure. The authors concluded that the proposed procedure using modified magnetic nanoparticles has some advantages, among them being the minimization of blood matrix effects during analysis.…”
Section: Diagnostic Application Of Mnpsmentioning
confidence: 99%
“…Yang et al (2021) used magnetic‐modified nanoparticles for the detection of eight drugs in human blood, obtaining recovery rates of 79.5%–99.9% and LOQs of 0.14–1.03 ng/mL (Yang et al, 2021). Polypyrrole/magnetic nanoparticles composite was evaluated as a sorbent for dispersive micro‐solid‐phase extraction of antidepressant drugs from biological fluids in the work of Asgharinezhad et al (2015).…”
Section: Green Sorbentsmentioning
confidence: 99%
“…This technique prevents the formation of agglomerates that may reduce the surface area, thus the adsorption capacity (Agarwal et al, 2019;Ghaemi et al, 2015;Jadhav et al, 2019;Weldegebrieal, 2020). Yang et al (2021) used magnetic-modified nanoparticles for the detection of eight drugs in human blood, obtaining recovery rates of 79.5%-99.9% and LOQs of 0.14-1.03 ng/mL (Yang et al, 2021). Polypyrrole/magnetic nanoparticles composite was evaluated as a sorbent for dispersive micro-solid-phase extraction of antidepressant drugs from biological fluids in the work of Asgharinezhad et al (2015).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Therefore, in recent years, several attempts were made to replace the mentioned routine methods with new and efficient approaches [5]. Up to now, different sample preparation methods like dispersive liquid-liquid microextraction [6], liquid-phase microextraction [7], solid-phase extraction [8,9], solid-phase microextraction [10], magnetic solid-phase extraction [11], liquid-liquid extraction [12,13], and dispersive solid-phase extraction (DSPE) [14,15] were used as the sample preparation methods before drug analysis. Among the mentioned methods, DSPE has some features such as simplicity, easiness, and inexpensiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of nanomaterials as the sorbents in DSPE has been widely investigated due to their unique physical and chemical properties including high thermal resistance, high surface area, and good mechanical strength [11]. Furthermore, the use of magnetic nanomaterials that are collected by an external magnet without the need for centrifugation reduces adsorption and desorption times [13]. Different magnetic nanoparticles were prepared based on carbonnanotubes [16], graphene [17], graphene oxide [18,19], silica [20], metal organic frameworks (MOFs), etc.…”
Section: Introductionmentioning
confidence: 99%